Perbaikan Kinerja Supply Chain Perusahaan Keripik Singkong Berdasarkan Analisis Product Availability - Parama Tirta Wulandari Wening Kusuma; Kuncoro Harto Widodo; Didik Purwadi (agriTECH, 2010)
Level of the product availability becomes a problem at the company, because of the fluctuation and the uncertainty of demand from the consumer and happened when the company determined the cycle service level which is the indica- tor of supply chain performance in fulfilling the availability of the product and avoiding either stock out or over stock in replenishment cycle. This research was conducted at UD As-Salam. The aim was to improve supply chain perfor- mance through determining the optimal cycle service level of product availability. Therefore, it was needed to set up the optimal level of product availability to optimize the profit. There were some steps that were taken in this research: determining the optimal cycle service level, optimal order size, expected profit, and sensitivity analysis between optimal cycle service level and expected profit. The result showed that the cost of under stocking and over stocking were 4,144 rupiahs and 6,573 rupiahs, respectively. The optimal cycle service level was 63 % with optimal order size was 2,842 kgs/month. This value improves the company’s profit in the amount of 11,043,570 rupiahs. The improvement of supply chain performance based on product availability analysis could increase profit up to 127,891 rupiahs.ABSTRAKLevel ketersediaan produk menjadi permasalahan pada objek penelitian ini karena adanya fluktuasi dan ketidak- pastian permintaan dari konsumen yang timbul ketika pelaku usaha telah menentukan cycle service level. Hal ini menjadi indikator kinerja supply chain dalam memenuhi ketersediaan produk dan menghindari kekurangan stok atau- pun kelebihan stok di siklus replenishment. Penelitian dilakukan di UD As-Salam, dan bertujuan untuk memperbaiki kinerja supply chain dari sisi product availability. Perlu ditetapkan optimal level of product availability agar mampu mengoptimalkan profit. Metode yang digunakan adalah dengan penentuan optimal cycle service level, optimal order size, expected profit, dan analisis sensitivitas terhadap optimal cycle service level dengan expected profit. Hasil peneli- tian menunjukan bahwa nilai cost of understocking adalah Rp 4.144,00 dan cost of overstocking adalah Rp 6.573,00. Nilai optimal cycle service level dapat dicapai pada level 63% dengan optimal order size 2.842 kg per bulan. Nilai ini mampu memberikan profit sebesar Rp 11.043.570,00. Peningkatan kinerja berdasarkan analisa product availability akan  memberikan peningkatan profit sebesar Rp 127.891,00 pada perusahaan.